Using surveillance data to monitor entry into care of newly diagnosed HIV-infected persons: San Francisco, 2006-2007 - Philip Susan; Marcus Julia L; Ahrens Katherine; Bernstein Kyle; Zetola Nicola M; Nieri Giuliano; Jones Diane; Hare C Bradley; Hsu Ling; Scheer Susan; Klausner Jeffrey D (BMC, 2009)
Abstract Background Linkage to care after HIV diagnosis is associated with both clinical and public health benefits. However, ensuring and monitoring linkage to care by public health departments has proved to be a difficult task. Here, we report the usefulness of routine monitoring of CD4 T cell counts and plasma HIV viral load as measures of entry into care after HIV diagnosis. Methods Since July 1, 2006, the San Francisco Department of Public Health (SFDPH) incorporated monitoring initial primary care visit into standard HIV public health investigation for newly diagnosed HIV-infected patients in select clinics. Entry into care was defined as having at least one visit to a primary HIV care provider after the initial diagnosis of HIV infection. Investigators collected reports from patients, medical providers, laboratories and reviewed medical records to determine the date of the initial health care visit after HIV diagnosis. We identified factors associated with increased likelihood of entering care after HIV diagnosis. Results One -hundred and sixty new HIV-infected cases were diagnosed between July 1, 2006 and June 30, 2007. Routine surveillance methods found that 101 of those cases entered HIV medical care and monitoring of CD4 T cell counts and plasma HIV viral load confirmed entry to care of 25 more cases, representing a 25% increase over routine data collection methods. We found that being interviewed by a public health investigator was associated with higher odds of entry into care after HIV diagnosis (OR 18.86 [1.83-194.80], p = .001) compared to cases not interviewed. Also, HIV diagnosis at the San Francisco county hospital versus diagnosis at the county municipal STD clinic was associated with higher odds of entry into care (OR 101.71 [5.29-1952.05], p < .001). Conclusion The time from HIV diagnosis to initial CD4 T cell count, CD4 T cell value and HIV viral load testing may be appropriate surveillance measures for evaluating entry into care, as well as performance outcomes for local public health departments' HIV testing programs. Case investigation performed by the public health department or case management by clinic staff was associated with increased and shorter time to entry into HIV medical care.